“If less is more, how you keeping score?” Outlines of a life cycle assessment method to assess sufficiency - André, Hampus (Frontiers in Sustainability, 2024)
It is increasingly clear that reaching environmental sustainability requires not only efficiency (reduced environmental impact per functionality) but also sufficiency measures (reduced environmental impact through reduced or changed functionality). Life cycle assessment (LCA) is a widely used tool to study environmental impacts related to consumption. However, because of the LCA convention of only comparing alternative products with equal functionality, it is currently inept as a method for assessing the environmental impacts of sufficiency measures. Against this background, this short paper aims to stimulate a discussion on how sufficiency measures can be assessed with LCA methodology. By analyzing the very few LCAs of explicit sufficiency measures in terms of the components of a functional unit (what function is provided, how much, for how long and how well) features of a potential new branch of LCA methodology, Sufficiency LCA, are outlined. In Sufficiency LCA, product alternatives need to be similar enough so that the what component of the functional unit can be equal, while the other components, how much, how long and how well, are allowed to be non-equal. Thus, a key feature of Sufficiency LCA concerns functional non-equivalence of compared product alternatives, which is not allowed or neglected in conventional LCA, but which could be allowed, acknowledged and quantified in Sufficiency LCA. Developing Sufficiency LCA could be critical considering that sufficiency measures are expected to be required, and that LCA is expected to be serviceable as decision-making support, in the transition towards environmental sustainability.